Pharmacokinetics of genistein distribution in blood and retinas of diabetic and non-diabetic rats. (August 2021) - Hakami, T.; Mahmoud, M.I.; de Juan, E.; Cooney, M.
Abstract: Genistein, a natural tyrosine kinase inhibitor, may act as an intraocular antiangiogenic agent. Its therapeutical use, however, is limited by its nonlinear pharmacokinetics. We aimed to determine genistein's kinetics and retinal tissue distributions in normal and diabetic rats. We developed an isocratic, reverse-phase C18 HPLC system to measure genistein concentration in blood and retinas of streptozotocin (65 mg/kg IV)-diabetic and non-diabetic rats receiving two types of genistein-rich diet (150 and 300 mg/kg) for ten days. Genistein's decay exhibited a two-compartmental open model. Half-lives of distribution and elimination were 2.09 and 71.79 min, with no difference between groups. Genistein steady-state concentration in blood for 150 and 300 mg/kg diet did not differ between diabetic (0.259 ± 0.07 and 0.26 ± 0.06 μg/ml) and non-diabetic rats (0.192 ± 0.05 and 0.183 ± 0.09 μg/ml). In retina, genistein concentration was significantly higher in diabetic rats (1.05 ± 0.47 and 0.997 ± 0.47 μg/gm wt. vs. 0.087 ± 0.11 and 0.314 ± 0.18 μg/gm wt., p < 0.05). The study determined that increasing genistein dose did not change its bioavailability, perhaps due to the poor aqueous solubility. The retina's increased genistein could be due to increased permeability of blood-retinal barrier that occurs early in diabetes.